ANALISIS PERUBAHAN PITA FREKUENSI 1800 DAN 2100 MHZ TERHADAP PERFORMANSI JARINGAN BASE TRANSCEIVER STATION - Syarif Muhammad Faisal . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2017)
Abstract - In its application, the mobile system has its limitations    and is    often    experienced disturbances  (interference)  like  limited  talk channels as the result of the increasing number of cellular communication technology user, which is led to „block call‟. The problem with Radio Frequency   (RF)   signal   reception   is   also   an important factor in wireless communication system. The low quality of signal levels caused the frequent call failure or „drop call‟. Therefore, it is necessary to have sustainable monitoring system and analysis towards the performance of the  network system, especially after the government produce the For a review of Necessary Process Monitoring and analysis of the Sustainable Network system, especially with the regulation of the Ministry of Communication  and  Information  No.  19  /  2013 About  "  Mekanisme  dan  Tahapan  Pemindahan Alokasi Pita Frekuensi Radio Pada Penataan Menyuluruh Pita Frekuensi Radio 2100 MHz.” The monitoring and performance analysis used Key Performance Indicator (KPI) parameters as a benchmark for the network performance and a description   of  the   cellular   system  Quality   of Service (QoS). The KPI parameters are Call Setup Success Rate (CSSR), Drop Call Rate (DCR), Handover Success rate (HSR), and Traffic Channel Congestion rate (TCH Congestion rate). The results of the test drive of five BTS before and after frequency refarming in 1800 and 2100 MHz, the percentage of SDCCH blocking was not high enough, as determined by PT. Indosat Ooredoo, which is not more than 2%. There are 5 BTS to be observed:   BTS  Nipah  Kuning,   BTS  Perum  1 Jeruju, BTS Martadinata, BTS Gertak 1 and BTS Gang Semangka.   Keywords  : Frequency band and Parameter Key Performance Indicator (KPI)